Membangun Generasi Berintegritas Pendidikan Karakter dalam Kurikulum Nasional di Sekolah Dasar - Cut Kumala Sari; Rahelsa Rahelsa; Abdul Jabar (Lembaga Pengembangan Kinerja Dosen, 2025)
Education is an important character foundation in forming a generation of the nation with integrity, honesty, and responsibility. In the context of the national curriculum, educational character has been integrated as part of the national education goals that not only emphasize cognitive aspects, but also affective and psychomotor. This article aims to examine the role of educational character in building a generation with integrity through a literature study approach to various educational policies and theories of character education. The results of the study show that the implementation of educational character in the national curriculum, such as through the 2013 Curriculum and the Merdeka Curriculum, has provided space for strengthening values ​​such as honesty, hard work, tolerance, and responsibility. However, challenges remain in its implementation, especially related to the consistency of implementation in schools, the readiness of educators, and the measurement of non-academic results. Therefore, synergy between schools, families, and communities is key to creating an effective character education ecosystem. This study recommends the need for intensive training for teachers and a more comprehensive curriculum evaluation to ensure that educational character truly forms students with integrity.